DIFFERENCES ANALYSIS OF SHARE LIQUIDITY AND RETURN OF SHARES BEFORE AND AFTER SHARE RESOLUTION OF INDUSTRIAL COMPANIES: ANALISIS PERBEDAAN LIKUIDITAS SAHAM DAN RETURN SAHAM SEBELUM DAN SESUDAH PEMECAHAN SAHAM PERUSAHAAN INDUSTRI - fenisi resty (International Journal of Management and Business (IJMB), 2023)
Stock splitting is a company strategy carried out in the capital market to attract potential investors. The more investors who make legal transactions, the trading volume of shares will increase. The population and sample in this study were companies that did split the sample listed on the Indonesia Stock Exchange for the 2014-2018 period. Using purposive sampling technique. The data analysis method used was descriptive statistical test, normality, and hypothesis. The result of the research is that the first hypothesis, stock split, there is no significant difference to Trading Volume Activity in the second hypothesis, there is no significant difference to the Abnormal Return.